2021
DOI: 10.1371/journal.pone.0248585
|View full text |Cite
|
Sign up to set email alerts
|

HIV testing behaviors and willingness to receive oral rapid HIV testing among dental patients in Xi’an, China

Abstract: Introduction HIV testing is an important strategy for controlling and ultimately ending the global pandemic. Oral rapid HIV testing (ORHT) is an evidence-based strategy and the evidence-based shows is favored over traditional blood tests in many key populations. The dental setting has been found to be a trusted, convenient, and yet untapped venue to conduct ORHT. This study assessed the HIV testing behaviors and willingness to receive ORHT among dental patients in Xi’an, China. Methods A cross-sectional surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This fi nding is consistent with a previous study which reported a relationship between participants' monthly income and HIV/AIDS knowledge scores. 14 The authors reported that a higher monthly income was associated with higher HIV/AIDS knowledge and that this collectively resulted in higher testing rates. 14 Similarly, Lopez-Quintero et al reported that patients' HIV knowledge was linked to previous exposure to HIV testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This fi nding is consistent with a previous study which reported a relationship between participants' monthly income and HIV/AIDS knowledge scores. 14 The authors reported that a higher monthly income was associated with higher HIV/AIDS knowledge and that this collectively resulted in higher testing rates. 14 Similarly, Lopez-Quintero et al reported that patients' HIV knowledge was linked to previous exposure to HIV testing.…”
Section: Discussionmentioning
confidence: 99%
“…14 The authors reported that a higher monthly income was associated with higher HIV/AIDS knowledge and that this collectively resulted in higher testing rates. 14 Similarly, Lopez-Quintero et al reported that patients' HIV knowledge was linked to previous exposure to HIV testing. 15 This reiterates the importance of HIV/AIDS-related dental education especially in areas of high infection rates.…”
Section: Discussionmentioning
confidence: 99%